Design of an Optimal Controller for the Roll Stabilization of Surface Ships with Active Fins - Arslan, M. Selcuk (CHAMBER MARINE ENGINEERS, 2018)
In this paper, an optimal controller is designed to control the undesired roll motion of a ship under the effect of sea waves by using active fin stabilizers. The roll dynamics is described by a single-degree-of-freedom nonlinear model. An actuator dynamics is also included to the dynamic system. Sinusoidal and random wave models are used to describe the wave elevation that causes disturbance moments in the ship. A worst-case scenario is the application of the periodic wave to bring the ship resonance, whereas the random waves are used to test the system at the smooth and moderate sea states. In designing the controller, the energy optimal control method, which allows both the closed-loop and real-time control of dynamic systems, is employed, and the control law is obtained analytically. The performance of the controller, under the effect of environmental disturbances, is tested by computer simulations and the results are compared with those from LQR controlled ship.
Keywords: Ship roll motion; Fin stabilizer; Optimal control; Roll damping; Engineering; Transportation